Texture Perception and Chewing of Agar Gel by People with Different Sensitivity to Hardness - Vasily Smirnov; Daria Khramova; Elizaveta Chistiakova; Natalya Zueva; Fedor Vityazev; Inga Velskaya; Sergey Popov (Gels)
Hardness is one of the dominant sensory characteristics of food. This study estimated the effect of sensitivity to hardness on the texture perception and chewing function using 2, 4, and 6% agar gels. Increasing the concentration of agar resulted in an increase in gel hardness and springiness, measured by texture profile analysis. Non-trained participants (n = 95) reported more subjective hardness and springiness during chewing gel samples as the agar concentration increased. Based on the relationship value of the instrumental and sensory data, all participants were divided into low-, medium-, and high-sensitivity groups (n = 25, 44, and 26). Low sensitivity to hardness was associated with low sensitivity to brittleness, springiness, chewiness, moisture, and swallowability. In all three groups, enhanced agar gel hardness increased the temporal chewing characteristics in a similar manner. However, in those with a high hardness sensitivity, the area amplitude of the masseter and temporalis muscles grew to a lesser extent than in those with a low or medium sensitivity. The activity of the suprahyoid muscles increased with the increasing agar gel hardness, regardless of sensitivity. All groups showed a similar salivation and bolus fragmentation while chewing gel. Thus, people’s sensitivity to hardness was associated with different perceptions of the gel’s textural properties and changes in masticatory muscle activity.